La “science des engrais” et le monde agricole en France au dix-neuvième siècle - Sacha Tomic (Journal for the History of Environment and Society, 2017)
This article examines the implementation and the spreading of a quality regulation system on fertilizers - in particular those stemming from recycling - in nineteenth-century France, in connexion with the question of their impact on the environment. In a first part I discuss the crucial role of chemists-agronomists in the establishment of a “science of fertilizers”. Practices gradually developed by chemical experts underpinned the establishment of official methods as sanctioned by the law of 7 April, 1888 on the repression of fraud in the trade of fertilizers. The fast technical evolution and methodological uncertainties of the chemical analyses were periodically criticized by some agronomists. Institutional laboratories were soon organized and were crucial in the establishment of a new general law on the repression of fraud on 1 August, 1905 which took into account the evolutionary character of analytical methods. In a second part, I examine the implementation of this “science-based fertilizers” within the agricultural world. First of all, the role of educational institutions is analyzed. Elementary and secondary school teachers proved crucial as intermediators, providing a simplified version of agricultural science which incorporated the traditional know-how of farmers. This strategy of mass propaganda was also framed in an emerging policy of regulating unhealthy establishments. Secondly, I will concentrate on the management of hazards related to fertilizers. Those fertilizers stemming from recycling were especially dangerous and could damage the health of both farmers and domestic animals. Fertilizers’ toxic effects were observed from the very beginning of their use. Physicians and toxicologists periodically reported accidents. They alerted farmers and sometimes took preventive measures. The pollution of groundwater by the spread of human fertilizers even was at the origins of the introduction of the word “pollution” in French legislation through the law of 15 February, 1902 relative to the protection of public health.